ANALISIS KEBUTUHAN PARKIR KAMPUS PASCASARJANA UNIVERSITAS BANDAR LAMPUNG - Chandra Alip Pratama (CV. KAMPUS AKADEMIK PUBLISING, 2026)
The Postgraduate Program of Universitas Bandar Lampung is one of the higher education institutions in Lampung, located in Bandar Lampung City, currently hosting four study programs. The interaction among students, staff, and lecturers generates a considerable volume of traffic movement that may cause congestion, so the provision of traffic-control facilities such as circulation and parking systems is essential. This study is limited to the analysis of parking demand and, more specifically, to the analysis of parking capacity improvement based on the calculation of parked-vehicle volume in the study area, using the indicators of parking duration, parking pattern, and parking capacity. Based on the data collection and analysis, the Postgraduate Campus of Universitas Bandar Lampung has a parking area of 9,566 m², with a total of 435 parking spaces (SRP) for passenger cars and 131 SRP for motorcycles. During lectures, parking demand reaches 166 cars and 218 motorcycles, while during graduation/wedding-reception events it reaches 531 cars and 202 motorcycles. The parking index is 0.96 for motorcycles and 0.67 for cars during lectures (indicating no problem), whereas during events it is 0.92 for motorcycles and 1.05 for cars, meaning the passenger-car parking facility is problematic because the index exceeds one.